Analisis Strategi Pemasaran Melalui Pendekatan Marketing Mix (Studi Kasus : Toko Ria Busana Cabang kota Cimahi) - Susilawati, Santi; Wibowo, Indrajati (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This research aims to analyze the marketing strategy implemented by Toko Ria Busana Cimahi using a marketing mix approach which includes four main elements: product, price, place and promotion (4P). This research uses a qualitative descriptive method with a case study approach. Data was collected through observation, interviews and documentation. The research results show that Toko Ria Busana maintains product quality through strict selection, sets competitive prices accompanied by loyalty programs such as member cards, chooses strategic locations that are easily accessible to consumers, and runs promotions through seasonal discounts. However, the implementation of digital marketing strategies is still limited. Therefore, it is recommended that Toko Ria Busana integrate digital marketing through the use of e-commerce, social media, online advertising, and collaboration with influencers to expand market reach and increase competitiveness in the industry.